Particle Image Velocimetry measurements inside a tapered roller bearing with an outer ring made of sapphire: Design and operation of an innovative test rig. (January 2022) - Maccioni, Lorenzo; Chernoray, Valery G.; Bohnert, Christof; Concli, Franco
Abstract: Experimental studies on rolling-element bearing lubrication represent an ambitious engineering challenge. In the present study, the design of a dedicated test rig to perform Particle Image Velocimetry (PIV) measurements on the lubricant inside a tapered roller bearing is presented. Through the usage of a sapphire outer ring, it has been possible to optically access the inside of a bearing without compromising its kinematics. PIV measurements allowed the reconstruction of the lubricant velocity field in the cavity between the cage and the outer ring at different rotational speeds. Results show that as the speed of rotation increases, bubbles due to aeration phenomena tend to appear and modify the behavior of the lubricant considerably. Highlights: Design of a test rig to perform PIV measurements into a tapered roller bearing. Experimentation at rotational speeds up to 2100 rpm in oil bath lubrication. Measurement of the lubricant velocity field near the cage through a sapphire outer ring. Observation of the increase of the aeration level with the increase of the rotational speed. Observation of the variation of the velocity field as the aeration level changes.